OsSDS is essential for DSB formation in rice meiosis - Wu, Zhigang; Ji, Jianhui; Tang, Ding; Wang, Hongjun; Shen, Yi; Shi, Wenqing; Li, Yafei; Tan, Xuelin; Cheng, Zhukuan; Luo, Qiong (Frontiers in Plant Science, 2015)
SDS is a meiosis specific cyclin-like protein and required for DMC1 mediated double-strand break (DSB) repairing in Arabidopsis. Here, we found its rice homolog, OsSDS, is essential for meiotic DSB formation. The Ossds mutant is normal in vegetative growth but both male and female gametes are inviable. The Ossds meiocytes exhibit severe defects in homologous pairing and synapsis. No γH2AX immunosignals in Ossds meiocytes together with the suppression of chromosome fragmentation in Ossds-1 Osrad51c, both provide strong evidences that OsSDS is essential for meiotic DSB formation. Immunostaining investigations revealed that meiotic chromosome axes are normally formed but both SC installation and localization of recombination elements are failed in Ossds. We suspected that this cyclin protein has been differentiated pretty much between monocots and dicots on its function in meiosis.